Penyimpangan Prinsip Kerjasama dalam Dialog Interaktif Roma Irama pada Acara Mata Najwa di Metro TV (Kajian Pragmatik) - Mudarman (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
Communication principles are included in the discussion of the relationship between speech and speaker. The aim of this research is to describe the forms of deviation from the maxims of quantity, quality, relevance and maxims of manner/implementation in Roma Irama's interactive dialogue on the Mata Najwa program on Metro TV. The method used in this research is descriptive qualitative. This research focuses on deviations from the principle of cooperation in Roma Irama's interactive dialogue on the Mata Najwa program on Metro TV which is studied pragmatically. Data was obtained using the listening method with the SBLC technique (skilled free-involved listening), recording technique, and note-taking technique. The data analysis method used is the matching method using pragmatic matching techniques. The results of this research found deviations from the principles of cooperation in the form of deviations from the maxim of quantity, maxim of quality, maxim of relevance, and maxim of method/implementation.